PROMOTION OF ACTIVE AND HEALTHY LIFESTYLE IN SCHOOL PHYSICAL EDUCATION CLASSES - Marinho de Andrade, Regiane dos Santos; Ferraz Amaral , Josária (RENEF, 2022)
Introduction: Obesity is a health risk, currently it is treated as an epidemic and that is why the WHO reports that it is a case of public health. Objective: to identify determinants of overweight and obesity in childhood. Method: The inclusion criteria were articles in Portuguese and published from 2010 to 2021, including original articles, cross-sectional studies, ecological studies and cohort. However, the exclusions were articles related to animals or adults, literature review, monographs, case studies and experimental studies or that worked on other underlying diseases that lead to obesity. In view of this, the study was carried out through a systematic literature review. Results: We analyzed a quantitative of 09 articles related to nutritional aspects and eating habits of children with obesity and childhood obesity as a public health problem. Where it was observed that most authors treat obesity as an epidemic, becoming a case of public health, which requires greater care, as it is a disease that brings many harm to children’s health and can last for life adulthood harming the quality of life. Conclusion: it became clear that all studies treat childhood obesity as an alarming and harmful subject to children’s lives, which at school is one of the highest rates of weight gain, due to the rampant consumption of ultraprocessed and sugars, that the family is the basis for improving eating habits and that physical activity and healthy eating make all the difference in reducing the rate of childhood obesity.